2019
DOI: 10.3390/ijerph16173015
|View full text |Cite
|
Sign up to set email alerts
|

The Use of HPLC-PDA in Determining Nicotine and Nicotine-Related Alkaloids from E-Liquids: A Comparison of Five E-Liquid Brands Purchased Locally

Abstract: E-liquid manufacturers are under scrutiny concerning the purity and concentration accuracy of nicotine and the minor nicotine-related alkaloids (NRAs) packaged in their products. In this communication we report concentrations of nicotine and five NRAs (nornicotine, cotinine, anabasine, anatabine, myosmine) from locally purchased E-liquids. Methods: Five brands of E-liquids (three bottles each) were purchased locally. Additionally, three bottles of reference E-liquid were prepared. Concentrations of nicotine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…No flavorings were added. The nicotine concentration per cigarette equivalent is higher than the typical concentration of nicotine in a tobacco cigarette but comparable to the high-end nicotine concentration found in a number of commercially available E-liquids [50]. E-liquid was aerosolized using a Tripl3 (Kennesaw, GA, USA) eGo style lithium ion battery (650 mAh, 3.7 V unregulated).…”
Section: E-liquid and Ecig Devicementioning
confidence: 88%
See 2 more Smart Citations
“…No flavorings were added. The nicotine concentration per cigarette equivalent is higher than the typical concentration of nicotine in a tobacco cigarette but comparable to the high-end nicotine concentration found in a number of commercially available E-liquids [50]. E-liquid was aerosolized using a Tripl3 (Kennesaw, GA, USA) eGo style lithium ion battery (650 mAh, 3.7 V unregulated).…”
Section: E-liquid and Ecig Devicementioning
confidence: 88%
“…Standard solutions of 99% (S)-(-)-nicotine, were prepared in BHI broth at concentrations of 0.4, 0.2, and 0.1 mg/mL. Standards and samples of BHI exposed to 25, 50, or 75 puffs of flavorless ECIG aerosol with nicotine or conventional cigarette smoke were analyzed by HPLC coupled with photodiode array detection, as previously described [49,50]. A Shimadzu HPLC system (Columbia, Standard solutions of 99% (S)-(-)-nicotine, were prepared in BHI broth at concentrations of 0.4, 0.2, and 0.1 mg/mL.…”
Section: High-performance Liquid Chromatography (Hplc) Of Nicotinementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that e-liquids containing nicotine used in ENDs are greatly variable than what are stated on labels [6][7][8][9][10][11][12][13][14][15]. Hence, Jordan Food and Drug Administration (JFDA) has recently issued specific legislations for tobacco and nicotine delivery systems including ENDs licensing and regulation in July 2019, which necessitate the utilization of reliable analytical methods to control these products and their contents for quality and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Since LC is a workhorse technique used for efficient and tedious analytical procedures [19][20][21]. It has been employed successfully for nicotine quantification in e-liquids such as liquid chromatography-mass spectrometry (LC-MS) [6,7], in addition to HPLC with photodiode array detection (HPLC-PDA) [13,14].…”
Section: Introductionmentioning
confidence: 99%